2021
DOI: 10.1002/jum.15873
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Assisted Doppler Features for Enhancing Thyroid Cancer Diagnosis

Abstract: Background This pilot study aims at exploiting machine learning techniques to extract color Doppler ultrasound (CDUS) features and to build an artificial neural network (ANN) model based on these CDUS features for improving the diagnostic performance of thyroid cancer classification. Methods A total of 674 patients with 712 thyroid nodules (TNs) (512 from internal dataset and 200 from external dataset) were randomly selected in this retrospective study. We used ANN to build a model (TDUS‐Net) for classifying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…[69] Recently, Zhu et al demonstrated a machine learning-based technique for enhancing diagnostic performance using US Doppler data acquired from 712 thyroid nodules (356 malignant and 356 benign). [70] They designed an artificial neural network model (TDUS-Net) by extracting features from US Doppler images (whole ratio, intranodular ratio, peripheral ratio, and the number of vessels) and US features defined by TI-RADS. For comparison, an additional artificial neural network model (TUS-Net) based on the US features alone was also designed.…”
Section: Doppler Ultrasound Imagingmentioning
confidence: 99%
“…[69] Recently, Zhu et al demonstrated a machine learning-based technique for enhancing diagnostic performance using US Doppler data acquired from 712 thyroid nodules (356 malignant and 356 benign). [70] They designed an artificial neural network model (TDUS-Net) by extracting features from US Doppler images (whole ratio, intranodular ratio, peripheral ratio, and the number of vessels) and US features defined by TI-RADS. For comparison, an additional artificial neural network model (TUS-Net) based on the US features alone was also designed.…”
Section: Doppler Ultrasound Imagingmentioning
confidence: 99%